Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Air Mineral Yeh Buleleng di Singaraja - Ni Kadek Dwi Darmayani; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine (1) the effect of price on purchasing decisions, (2) the effect of product quality on purchasing decisions, (3) and the effect of price and product quality on purchasing decisions. The population in this study, namely the community in Singaraja whose number is unknown and using the Ferdinand formula to determine the number of samples based on indicators using the Purposive sampling technique with the number of samples used as many as 140 people. The data collection method uses a questionnaire and analysis using multiple linear regression analysis. Hypothesis testing uses the t test and f test which are processed with the Statistical Package for The Social Science (SPSS) software version 25. The results of the study show that (1) price has a positive and significant effect on purchasing decisions for Yeh Buleleng mineral water, (2) product quality has a positive and significant effect on purchasing decisions for Yeh Buleleng mineral water, (3) price and product quality have a positive and significant effect on purchasing decisions for Yeh Buleleng mineral water.